Platelet count and platelet indices in patients of pregnancy-induced hypertension at a rural tertiary care hospital in western India (Journal of Pathology of Nepal, 2023)
Background: Pregnancy-induced hypertension is a serious complication during pregnancy causing maternal and fetal morbidity and mortality. Pregnancy-induced hypertension associated with thrombocytopenia can help in predicting the severity of the disease. The study aimed to study the platelet count, and platelet indices in Pregnancy induced hypertension patients and compare them with normotensive pregnant women. Materials and methods: This was a case control study, conducted on patients visiting antenatal care (ANC) at a Tertiary care rural hospital in western India. Study population included a total of 82 patients, which were divided into 2 groups with 41 patients in each control (healthy pregnant women) and study groups (pregnant women with PIH). Patients with chronic hypertension and known case of thrombocytopenia were excluded from the study. The blood samples collected were processed on fully automated cell counter for estimation of platelet count and indices.Results: The platelet count in the study group ranged from 186434.1±81086.9 whereas in the control group it was 268659±72206.9, showing that the platelet count was significantly lower in women with Pregnancy induced hypertension than in the control group. The MPV, PDW, systolic BP, diastolic BP was found to be significantly elevated in the study group as compared to the control group.Conclusions: The present study concludes that blood parameter such as platelets count and platelet indices can be considered as an early, economical and easily available parameter for assessment of severity of PIH cases.